Stereotactic Body Radiation Therapy for Stage I Non-Small Cell Lung Cancer: A Small Academic Hospital Experience - Factor, Oren B.; Vu, Charles C.; Schneider, Jeffrey G.; Witten, Matthew R.; Schubach, Scott L.; Gittleman, Alicia E.; Catell, Donna T.; Haas, Jonathan A. (Frontiers in Oncology, 2014)
Purpose/Objective(s): Stereotactic body radiation therapy (SBRT) has been shown to have increased local control and overall survival relative to conventional external beam radiation therapy in patients with medically inoperable stage I non-small cell lung cancer (NSCLC). Excellent rates of local control have been demonstrated both in clinical trials as well as in single-center studies at large academic institutions. However, there is limited data on the experiences of small academic hospitals with SBRT for Stage I NSCLC. The purpose of this study is to report the local control and overall survival rates in patients treated with SBRT for Stage I NSCLC at Winthrop-University Hospital (WUH), a small academic hospital. Materials/Methods: This is a retrospective review of 78 Stage I central and peripheral NSCLC tumors treated between December 2006 and July 2012 with SBRT at WUH. Treatment was given utilizing fiducials and a respiratory tracking system. If the fiducials were not trackable, a spine tracking system was used for tumor localization. CT-based planning was performed using the ray trace algorithm. Treatment was delivered over 4 consecutive days for central tumors to a dose of 4800 cGy delivered in 4 fractions. Peripheral tumors were treated to a dose of 6000 cGy in 3 consecutive fractions. The Kaplan-Meier method was used to calculate local control and overall survival. Results: The median age was 78.5 years. 54% of the patient population was female. 67% of the tumors were Stage IA, and 33% of the tumors were Stage IB. 53% of the tumors were adenocarcinomas and 29% were squamous cell carcinomas, with the remainder being of unknown histology or NSCLC, not otherwise specified The 2-year local control rate was 87%, and the two-year overall survival was 68%. Conclusions: Our findings support that local control and overall survival at a small academic hospital are comparable to that of larger academic institutions' published experiences with SBRT for Stage I NSCLC.